Longitudinal Assessment of “User-Driven” Library Commons Spaces - Fox, Robert; Doshi, Ameet (Evidence Based Library and Information Practice, 2013)
Objective – To conduct a longitudinal assessment of library spaces at the Georgia Tech Library and to determine the satisfaction of students with the most recent commons renovation. The library has completed three commons area renovations. The Library West Commons (LWC) opened in 2002 with an individual productivity lab, multimedia studio, and presentation rehearsal studio, while the Library East Commons (LEC) and the 2nd floor West Commons (2 West) opened in 2006 and 2009, respectively, with flexible, user-centered environments designed to promote collaborative activities. This analysis focuses on the renovated collaborative spaces, while also investigating and commenting on how renovation impacts usage of other spaces in the library. Methods – Usage of all library spaces was measured during one-week periods in Fall 2008 and Spring 2010. Observations were made of each student floor in the library at four times during the day; measures included space utilization by groups, group sizes, and laptop utilization. In addition, a qualitative instrument was administered during Spring 2010 to 103 students using the 2 West Commons space to confirm whether the renovation met their needs. Results – Overall, there was a 64.5% increase in group utilization of the library from 2008 to 2010, driven primarily by the 2 West renovation. The greatest concentration of group usage was in the LEC and 2 West, though the number of groups using the LEC declined. Laptop use in the 2 West commons more than doubled (33.6% to 70.5%), and laptop use in the entire library increased from 40.5% to 49.0%. In the qualitative survey, scores ranged between 4.0 and 5.0 on a 5-point scale for items regarding four design themes for the 2 West renovation: power/data, lighting, aesthetics, and the creation of a “defined yet open” space. Conclusion – Findings suggest that the 2 West Commons is attracting more students and groups following its renovation, that it is attracting students and groups away from the previously renovated LEC, and that overall usage of the library increased subsequent to the 2 West renovation.